2011
DOI: 10.1021/jp208018r
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemistry of Halomethanes CFnBr4–n (n = 0–3) Based on iPEPICO Experiments and Quantum Chemical Computations

Abstract: Internal energy selected bromofluoromethane cations were prepared and their internal energy dependent fragmentation pathways were recorded by imaging photoelectron photoion coincidence spectroscopy (iPEPICO). The first dissociation reaction is bromine atom loss, which is followed by fluorine atom loss in CF(3)Br and CF(2)Br(2) at higher energies. Accurate 0 K appearance energies have been obtained for these processes, which are complemented by ab initio isodesmic reaction energy calculations. A thermochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2

Year Published

2013
2013
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 61 publications
2
35
2
Order By: Relevance
“…In such cases, the parent signal is always less than 100 %, and there is significant daughter ion signal, even at the ionization limit. This effect had been observed previously [17], and was first discussed in the TPEPICO study of CFBr 3 and CBr 4 [11].…”
Section: ð4:1þsupporting
confidence: 72%
See 4 more Smart Citations
“…In such cases, the parent signal is always less than 100 %, and there is significant daughter ion signal, even at the ionization limit. This effect had been observed previously [17], and was first discussed in the TPEPICO study of CFBr 3 and CBr 4 [11].…”
Section: ð4:1þsupporting
confidence: 72%
“…Firstly, that CF 4 , CHF 3 , CFCl 3 and CCl 4 which are not included in this study, dissociatively photoionize forming no initial parent ion, and one can regard the ion potential well depths as so shallow they do not exist. In another study on CF n Br 4-n , Bodi et al [11]. found that CBr 4 + is formed and dissociated into CBr 3 + ?…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations